2005
DOI: 10.2139/ssrn.673604
|View full text |Cite
|
Sign up to set email alerts
|

Market Power in Direct Marketing of Fresh Produce: Community Supported Agriculture Farms

Abstract: Abstract:CSA farms establish a loyal customer base and, potentially, market power. A new empirical industrial organization (NEIO) approach and survey data from Northeast CSA farms are used to determine whether CSA farms have market power and the extent to which they exercise their market power. Results suggest CSA farms exert about two percent of their potential monopoly power. Abstract: CSA farms establish a loyal customer base and, potentially, market power. A new empirical industrial organization (NEIO) app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…As a counter to this high level of market power among shoppers we found that customer loyalty provided farmers markets with an advantage. This is consistent with the factors that Lass et al (2005) found: higher customer loyalty improved a CSA's ability to capture more profits. " [T]he nature of their products, i.e., fresh organic vegetables produced from a known source, is such that consumer loyalty and 'brand' recognition make consumers captive to a given farm" (p. 5).…”
Section: Competitive Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…As a counter to this high level of market power among shoppers we found that customer loyalty provided farmers markets with an advantage. This is consistent with the factors that Lass et al (2005) found: higher customer loyalty improved a CSA's ability to capture more profits. " [T]he nature of their products, i.e., fresh organic vegetables produced from a known source, is such that consumer loyalty and 'brand' recognition make consumers captive to a given farm" (p. 5).…”
Section: Competitive Analysissupporting
confidence: 83%
“…They mention such strategies as operating on different days from nearby markets, extending the operating season, and building upon location-specific features (e.g., nearby businesses, parks, access to parking). Another exception is Lass, Lavoie, and Fetter (2005), whose study of Community Supported Agriculture (CSA) is directly relevant to farmers markets. They conclude that CSA operations have the ability to turn customer loyalty and ideological relations with customers into profits.…”
Section: Competitive Analysismentioning
confidence: 99%
“…Despite an abundance of different structural models and methods developed for the analysis of market power, a closer look at the articles published in the past three decades reveals that the range of methods used empirically is limited to only two approaches, namely PTA and GIM (Sheldon and Sperling, ; Lass et al ., ). The first widely used approach for measuring the degree of oligopoly power is the PTA pioneered by Appelbaum () in the analysis of the Canadian food processing industry and further elaborated by Lopez ().…”
Section: Review Of Empirical Studies Of Market Power In the Agricultumentioning
confidence: 97%
“…Previous research, however, attests to the unsatisfactory improvement of local economy (e.g. Lass, Lavoie & Fetter, 2005). The relative importance of local sales or local supply chains is related to factors such as the company's size, its geographic location, e.g.…”
Section: Economic Benefitsmentioning
confidence: 99%